Pullout Behavior of Different Geosynthetics—Influence of Soil Density and Moisture Content - Ferreira, Fernanda Bessa; Vieira, Castorina Silva; Lopes, Maria de Lurdes (Frontiers in Built Environment, 2020)
Geosynthetics have increasingly been used as reinforcement in permanent earth structures, such as road and railway embankments, steep slopes, retaining walls and bridge abutments. The understanding of soil-geosynthetic interaction is of primary importance for the safe design of geosynthetic-reinforced soil structures, such as those included in transportation infrastructure projects. In this study, the pullout behaviour of three different geosynthetics (geogrid, geocomposite reinforcement and geotextile) embedded in a locally available granite residual soil is assessed through a series of large-scale pullout tests involving different soil moisture and density conditions. Test results show that soil density is a key factor that affects the reinforcement pullout resistance and the failure mode at the interface, regardless of geosynthetic type or soil moisture content. The soil moisture condition may considerably influence the pullout response of the geosynthetics, particularly when the soil is in medium dense state. The geogrid exhibited higher peak pullout resistance than the remaining geosynthetics, which is associated with the significant contribution of the passive resistance mobilised against the geogrid transverse members to the overall pullout capacity of the reinforcement.